Marketing strategies to project carsem as the best semiconductor subcontractor in the world / Azmi Mohd Isa - Mohd Isa, Azmi (1991)
Electronic industries industry is one of the fastest growing in the world. The derived demand for semiconductor devices as the building block of electronic industries, is rapidly increasing. As production increases, the pressure toward lower price, higher quality and fast delivery also increased. To handle this demand, lower.ing the cost is one of the best solutions. By having offshore sub-contract assembly, electronic firm <semiconductor industries) can reduce their cost and survive in this competitive world. There are more than 50 sub-contract assembly companies in this world. Their goal is to be the best runong the best. Carsem (M) Sdn Bhd has portrayed excellent marketing strategies to project Carsem as the best semiconductor subcontractor in the world. The report begins with a look at the electronic industry as a whole and semiconductor's position in the electronic industries. Attention would also be given as to when the semiconductor subcontractor business/services come:- and how much companies plan their strategies to be the best in the world.